1986
DOI: 10.1021/bi00370a001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ethanol-inducible human liver N-nitrosodimethylamine demethylase

Abstract: Through the use of monospecific antibodies directed against hepatic cytochrome P-450j, an enzyme induced in rats treated with ethanol or isoniazid, we have purified from human liver the related cytochrome P-450 termed HLj. HLj resembles rat P-450j and P-450 LM3a, the homologous cytochrome in rabbit liver, in its NH2-terminal amino acid sequence, in being in highest concentration in liver microsome samples prepared from two patients intoxicated by ethanol and one patient given isoniazid, and in catalyzing the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(67 citation statements)
references
References 19 publications
(20 reference statements)
5
62
0
Order By: Relevance
“…29) As listed in Table 1, 4-CBP increased CYP2E1 protein at various doses except for a high dose administration. All of these findings, [22][23][24][25][26][27][28][29] together with our findings ( Table 1), suggest that the increase in CYP2E1 protein by 4-CBP administration can be ascribed to the prevention of CYP 2E1 degradation, and perhaps to mRNA stabilization. However, further detailed study will be needed.…”
Section: Resultssupporting
confidence: 67%
“…29) As listed in Table 1, 4-CBP increased CYP2E1 protein at various doses except for a high dose administration. All of these findings, [22][23][24][25][26][27][28][29] together with our findings ( Table 1), suggest that the increase in CYP2E1 protein by 4-CBP administration can be ascribed to the prevention of CYP 2E1 degradation, and perhaps to mRNA stabilization. However, further detailed study will be needed.…”
Section: Resultssupporting
confidence: 67%
“…Absorbance spectra revealed that the purified CYP2E1 was in a mixed spin state, suggesting that in solution some CYP2E1 protein molecules have water bound to the sixth coordination site of the heme iron, but in other molecules the water is absent, and the heme iron is five-coordinate. Most mammalian P-450s are water-coordinated in the resting state, but this mixed spin state has previously been reported for full-length human CYP2E1, although it has also been isolated as either all high spin or all low spin (37)(38)(39)(40). When reconstituted with NADPH-cytochrome P-450 reductase and cytochrome b 5 , the truncated, purified CYP2E1 is catalytically competent in performing two classic CYP2E1 reactions: 2-hydroxylation of p-nitrophenol and 6-hydroxylation of chlorzoxazone (data not shown).…”
Section: Resultsmentioning
confidence: 76%
“…CYP2C8 has two access channels, one on each side of the BЈ helix (57). The channel in CYP2C9 exits between helices F and I and the C-terminal ␤ 4 sheet system (37). CYP2D6 has the same hydrophilic access channel as CYP2C9 and a second putative channel exiting between the G and I helices (58).…”
Section: Discussionmentioning
confidence: 99%
“…The inducibility of P450IIIA3 and P450IIE1, in human, has only been recently demonstrated (Watkins et al, 1985;Molowa et al, 1986;Wrighton et al, 1986).…”
Section: Introductionmentioning
confidence: 99%